Sistem Informasi Pelayanan Jasa Laundry Sepatu Pada Queen Shoes Cleaning - Syifa Nur Rakhmah; Irfan Rizki (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
Shoes are one of the complementary tools to support one's appearance, over time shoes become a very important aspect to pay attention to, the development of the times makes the shoe industry compete in innovation in terms of design or color. With the technology that has developed at this time, it can be used in all aspects of the industry, one of which is in the business or business sector at the Queen Shoes Cleaning store. The process used at this time is still carried out by recording services, making reports, and also storing transaction evidence manually so that the documents are messy. In the future, there is a very big risk of losing the documents in the store. For this reason, the author makes the idea of building a website-based information system in which you can order services, print reports, make receipts, and see shoe washing prices. There are 3 users in this system, namely regular visitors, registered visitors, and admins. For ordinary employees can only see the price list, about the store, the type of service. Then members can make transactions, print transaction receipts, and admins can process incoming transactions, print incoming reports, view user data, and view admin data. The method used in conducting this research is descriptive method, combining data collection methods and system development methods. With this website-based shoe washing service information system, it can help and simplify the shoe washing service process.